2020
DOI: 10.1002/sim.8529
|View full text |Cite
|
Sign up to set email alerts
|

A flexible nonlinear mixed effects model for HIV viral load rebound after treatment interruption

Abstract: Characterization of HIV viral rebound after the discontinuation of antiretroviral therapy is central to HIV cure research. We propose a parametric nonlinear mixed effects model for the viral rebound trajectory, which often has a rapid rise to a peak value followed by a decrease to a viral load set point. We choose a flexible functional form that captures the shapes of viral rebound trajectories and can also provide biological insights regarding the rebound process. Each parameter can incorporate a random effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Determining convergence appears to be an open question for StEM. In the literature, the commonly used approach for convergence diagnostics is through visual examination of the trace plots (see, e.g., Yang, 2018, Wang et al, 2020, Huang et al, 2020. Recently, Zhang et al (2020) proposed a Geweke Statistics based method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining convergence appears to be an open question for StEM. In the literature, the commonly used approach for convergence diagnostics is through visual examination of the trace plots (see, e.g., Yang, 2018, Wang et al, 2020, Huang et al, 2020. Recently, Zhang et al (2020) proposed a Geweke Statistics based method.…”
Section: Discussionmentioning
confidence: 99%
“…The StEM algorithm is more computationally efficient than the MCEM algorithm as only one realization of the missing data is required for each iteration (IP, 2002). Most recently, Wang et al (2020) extended the StEM algorithm to estimate parameters in VL dynamics models accounting for left-censored data; the authors showed that the resulting estimator is less biased than naive methods that either omit all censored data points or impute the censored observation with half of the quantification limit.…”
Section: Introductionmentioning
confidence: 99%
“…In general, clinical trial outcome measures and analysis methods are kept simple as discussed above but more complicated statistical modeling of viral rebound kinetics can also be applied [39,40]. However, these methods were developed using older ATI studies; substantive modeling complications might arise if applied to ATI trials with relatively short durations off ART such as studies with ART restart directly after viral rebound.…”
Section: Viral Set Pointmentioning
confidence: 99%
“…For the convergence of a StEM algorithm, in literature, the commonly used approach is through visually examination of the trace plots (see, e.g., [18], [19], [20]). Recently, Zhang et al [9] proposed a Geweke Statistics based method.…”
Section: The Estimation Proceduresmentioning
confidence: 99%